BELAJAR MENYENANGKAN DENGAN LAGU-LAGU BAHASA INGGRIS BAGI ANAK-ANAK PAUD - Puspita, Dayu Retno; Kurniawan, Eka Yulyawan; Fadilah, Ahmad Arif (Community Services and Social Work Bulletin, 2024)
This community service activity aimed to create an enjoyable learning experience by introducing English songs to children at KB/TK Kasih Ibu 05 in Periuk, Tangerang. During this activity, the instructor used direct and demonstration methods. The activities included obtaining implementation permits, preparing materials and tools, executing the program, and evaluating its effectiveness. The training began by introducing new vocabulary through English videos tailored to the level of KB/TK students. The children watched several English song videos, practiced pronunciation of the vocabulary with appropriate intonation, rhythm, and stress related to the songs, and concluded with singing English songs together with movements. It is hoped that after participating in this activity, the PAUD children will become familiar with English songs and that teachers can utilize simple English songs as a learning resource.